Mineralogical and Geochemical Investigations in the Perm State University (1916 – 2016) - R. G. Iblaminov (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2016)
The history of foundation and development of mineralogical and geochemical sciences on the Mineralogy and Petrography Department of the Perm State University for 100 years is presented. The achievements in the alluvial mineralogy and nanomineralogy are characterised. Relationship of development in the area of geochemical research on early stage with the European scientific school is discussed. The next stage is characterized by transition to investigations of trace elements and usage of the modern analytic base for environmental geochemistry. Petrographic and lithologic investigations have become the base for paleotectonic reconstruction of the Western Urals area. The study of distribution of mineral resources has been conducted on the base of specific minerageodynamic concept. The principles of minerageodinamic investigation of oil and gas basins, and methodology of reservoir study using modern technology were developed. The contribution of individual scientists in development in different scientific areas is illustrated.